Produksi Katup Motor, SS304, fBatang 5x95 mm, fPayung 29 dan 34 mm, Kapasitas 1 Pasang/Jam - Kevin Rabbani Akbar; Syamsul Hadi; Rifki Armanda Aji Saputra; Aldy Aditya Revanza; Diandra Galang Firmansyah (International Forum of Researchers and Lecturers, 2026)
The factory did not produce the intake valve and exhaust valve of motorcycle in 2013, cylinder volume 200 cm3 as a problem encountered in the field. The production objective is to obtain the intake valve and exhaust valve of motorcycle from steel material, SS304, 5x95 mm rod with 29 umbrella and 5x95 mm rod with 34 mm umbrella. The production method includes: design of the intake valve and exhaust valve of motorcycle from steel material, SS304, 5x95 mm rod, 29 and 34 mm umbrella; selection of SS304 raw materials; forging of the intake valve and exhaust valve; turning of umbrellas and valve stems; finishing-smoothing; quality-dimension-standard inspection. The production results are in the form of motorcycle intake valves and exhaust valves made of SS304 material, intake valves with 5x95 mm stems and 29 mm umbrellas and exhaust valves with 5x95 mm stems and 34 mm umbrellas with a total production cost of Rp. 160,000,-/pair, and a process duration of 60 minutes/long which has an impact that 2013 motorcycles, 200 cm3 cylinder volume can be re-functioned with these valves or the supply of intake valves and exhaust valves is available on the market.